A Comparison of Hematological, Immunological, and Stress Responses to Capture and Transport in Wild White Rhinoceros Bulls (Ceratotherium simum simum) Supplemented With Azaperone or Midazolam - Pohlin, Friederike; Hooijberg, Emma H.; Buss, Peter; Huber, Nikolaus; Viljoen, Francois P.; Blackhurst, Dee; Meyer, Leith C. R. (Frontiers in Veterinary Science, 2020)
Capture and transport are essential procedures for the management and conservation of southern white rhinoceroses (Ceratotherium simum simum), but are associated with stress-induced morbidity and mortality. To improve conservation efforts, it is crucial to understand the pathophysiology of rhinoceros stress responses and investigate drug combinations that could reduce these responses. In this study we measured rhinoceros stress responses to capture and transport by quantifying hematological and immunological changes together with adrenal hormone concentrations. We investigated whether the potent anxiolytic drug midazolam was able to mitigate these responses compared to azaperone, which is more commonly used during rhinoceros transport. Twenty three wild white rhinoceros bulls were transported for 6 hours (280 km) within the Kruger National Park for reasons unrelated to this study. Rhinoceroses were immobilized with either etorphine-azaperone (group A, n = 11) or etorphine-midazolam (group M, n = 12) intramuscularly (IM) by darting from a helicopter. Azaperone (group A) or midazolam (group M) were re-administered intramuscularly every two hours during transport. Serial blood samples were collected at capture (TC), the start of transport (T0) and after 6 hours of transport (T6). Changes in hematological and immunological variables over time and between groups were compared using general mixed models. Increases in plasma epinephrine and serum cortisol concentrations indicated that rhinoceroses mounted a stress response to capture and transport. Packed cell volume decreased from TC to T6 indicating that stress hemoconcentration occurred at TC. Neutrophils progressively increased and lymphocytes and eosinophils progressively decreased from T0 to T6, resulting in an increase in neutrophil to lymphocyte ratio; a characteristic leukocyte response to circulating glucocorticoids. A reduction in serum iron concentrations may suggest the mounting of an acute phase response. Rhinoceroses experienced a decrease in unsaturated fatty acids and an increase in lipid peroxidation products at capture and towards the end of transport indicating oxidative stress. Midazolam, at the dose used in this study, was not able to mitigate adrenal responses to stress and appeared to directly influence leukocyte responses.